Pengaruh Metode Belajar dan Konsep Diri terhadap Hasil Belajar Matematika Siswa - Mohamad Lutfi Nugraha (SAP (Susunan Artikel Pendidikan), 2019)
The purpose of this study was to determine the effect of learning methods with CTL on student mathematics learning outcomes, to determine the effect of students' self-concepts on student learning outcomes in mathematics, and to determine the effect of the interaction of learning methods with CTL and self-concepts. The experimental method was used in this study, which was located at Uswatun Hasanah Middle School in 2019, with 60 students being sampled, including 30 control class students and 30 experimental class students. Data was collected by distributing questionnaires directly to the sample. Data analysis uses descriptive statistics such as finding mean, median, mode, standard deviation, and inferential statistics, which is to find coefficients. The results showed: There is an influence of learning methods with CTL on student mathematics learning outcomes, there is an effect of students 'Self Concepts on student learning outcomes in mathematics, and there is an interaction of learning methods with CTL methods and students' Self Concepts on mathematics learning outcomes.